Multi-assay assessment of cytotoxicity reveals multiple mechanisms of action in 3D microtissues - Ahbid Zein-Sabatto; Katerina St. Angelo; Samantha J. Madnick; Diane Hoffman-Kim; Jeffrey R. Morgan; Jonghwan Lee (Scientific Reports)
Abstract Cell viability assays are an integral component of toxicology and high-throughput drug screening studies; however, many assays rely on a single biomarker of cell death which provides an incomplete assessment of cell viability. Here, we introduce an innovative approach that combines data from multiple assays using a linear mixed effects regression model and principal component analysis. We explored the cytotoxic response of various assay-treatment combinations using four assays with distinct mechanisms of action and seven different treatments across three types of microtissue cultures. The multi-assay data revealed the presence of multifaceted cellular injuries which highlight the need for multimodal approaches to better understand complex disruptions to viability. By incorporating outputs from the four assays, we introduced a new lethal concentration threshold that captures changes from different cellular injuries to provide a more comprehensive evaluation of cytotoxicity. Overall, the proposed approach provides a unique opportunity to analyze data from multiple assays in a holistic manner to improve the predictive power of drug screening and toxicology studies.